Restoration of law and order and justice in the de-occupied territories - VESELOV, Микола (Ius Modernum, 2023)
Introduction. Public order and internal security are a prerequisite for the rule of law, judicial protection of citizens’ rights, public administration and, accordingly, the reconstruction of liberated (de-occupied) territories. Problem. One of the primary tasks of the state after the de-occupation of Ukrainian regions is the restoration of the law enforcement system in these territories. The aim of the article is to determine the principles, stages and content of the restoration of the law enforcement and judicial system in the post-conflict (de-occupied) territories of Ukraine. Methods. Analytical reviews, scientific publications and monitoring of information about events in Ukraine in online publications and mass media became the empirical basis of the research. Thanks to the combination of general scientific and special methods of cognition, it was possible to process the specified empirical material and obtain our own scientific conclusions, which are correlated with the purpose and tasks of the article. Results. Restoring the functioning of the law enforcement and judicial system in the de-occupied territories of Ukraine is a necessary but long-term process. It should be carried out on the basis of certain principles, in particular, taking into account international experience and phasing. It was established that the restoration of the law enforcement and judicial systems in the de-occupied territories of Ukraine takes place according to its own scenario without the participation of the international police mission, in accordance with the unified national structure of these bodies. Conclusions. The restoration process is proposed to be divided into three stages, which, depending on specific regions, will include two options: 1) stabilization, constructive and adaptive (for territories occupied by the aggressor's troops after 02/24/2022 and liberated by the Armed Forces of Ukraine as a result of the counteroffensive; 2) stabilization, reconstructive and adaptive (for the territories of Donbass and Crimea, occupied since 2014). Each of the above stages has its own tasks, resources and implementation features.